2003
DOI: 10.1016/s0921-4534(03)00890-6
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional crossover of vortex dynamics induced by Gd substitution on Bi2212 single crystals

Abstract: The vortex dynamics of Bi 2 Sr 2 Ca 1−x Gd x Cu 2 O 8+δ single crystals is investigated by magnetic relaxation and hysteresis measurements. By substituting Ca with Gd, it is found that the interlayer Josephson coupling is weakened and the anisotropy is increased, which leads to the change of vortex dynamics from 3D elastic to 2D plastic vortex creep. Moreover, the second magnetization peak, which can be observed in samples near the optimal doping, is absent in the strongly underdoped ( with 2D vortex ) region.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This equation successfully applied to the doped/substituted BSCCO system previously by many groups [59][60][61][62][63][64][65]. Calculations for the unsubstituted Bi-2212 system had shown that the p value ranged from 0.16 to 0.22 [58].…”
Section: Hole Concentrationmentioning
confidence: 97%
“…This equation successfully applied to the doped/substituted BSCCO system previously by many groups [59][60][61][62][63][64][65]. Calculations for the unsubstituted Bi-2212 system had shown that the p value ranged from 0.16 to 0.22 [58].…”
Section: Hole Concentrationmentioning
confidence: 97%
“…Recently, this equation was successfully applied to the doped/substituted Bi-based superconducting system [56][57][58][59][60]. Previous calculations for the unsubstituted Bi-2223 material had shown that the P-value ranged from 0.116 to 0.16.…”
Section: Hole Concentrationmentioning
confidence: 99%
“…This formula is found to be applicable to several doped cuprate superconductors [19,[35][36][37][38][39][40][41][42]. The T max c value is taken from the experimental data, and using this relation, p values for all samples have been calculated; they are given in table 1.…”
Section: Resultsmentioning
confidence: 99%